Superstitious beliefs of science and non-science teachers in elementary and secondary schools - Rosario, Oscar Aquino 1945- (1978)
This study aimed to determine the influence of science teaching on the supertitious beliefs of teachers. The normative survey method was used in this study. One hundred (20 science high school, 20 non-science high school, 30 science elementary, and 30 non-science elementary) teachers in San Carlos City, Pangasinan selected through random sampling were involved in the study. A questionnaire-test constructed and developed by the researcher was used. The data gathered were then analyzed by the One-Way Analysis of Variance and the t-Test to determine the significance of the differences. In general, teachers believed in only a little more than one-fourth (26.23) of the 40 superstitious beliefs used. Science schools were less superstitious than those from non-science.
Vita.
Thesis (M.A. Elementary Science)--University of the Philippines, Diliman.
Keywords: Science teachers -- Philippines -- San Carlos City (Pangasinan) -- Attitudes; Elementary school teachers -- Philippines -- San Carlos City (Pangasinan) -- Attitudes; High school teachers -- Philippines -- San Carlos City (Pangasinan) -- Attitudes; Superstition -- Philippines